Community empowerment through the activation of early childhood education in Harapan Jaya Village, South Misool, Raja Ampat - Endra Putra Raharja; L. Latifah; Mutia Amanah; Yogi Indra Wijayanto; R. Riskawati; Liya Pransiska (Journal of Community Service and Empowerment, 2022)
Harapan Jaya is one of the villages in South Misool that has not been trained by the community empowerment program from the Higher Education Institution. Based on the results of observations and dialogues with the figures concerned, there were several problems in the location, including early childhood education. For this reason, community empowerment was carried out through the activation of Early Childhood Education in Harapan Jaya Village, South Misool. The method used by the team concerns the preparation, formulation, socialization and implementation of work programs. The results obtained by the team have succeeded in starting to reactivate Early Childhood Education which has been inactive for a long time. Various methods of preparation to implementation have been carried out well so that the residents are very enthusiastic about this program. Literacy training was given by the team to residents who would later become teachers in Early Childhood Education in this area. In addition, material and media assistance is also provided to prospective teachers so that this Early Childhood Education can continue independently.